PENENTUAN STATUS MUTU AIR DENGAN METODE STORET DIDANAU SENTANI JAYAPURA PROPINSI PAPUA - Walukow, Auldry F (BERITA BIOLOGI, 2010)
The problem in Lake Sentani area are degradation of watershead and land forest convertion, which cause decreasing water quality in Sentani Lake. For this reason, it is very important to analyze of water quality status in L. Sentani periodically in order to retain its sustainability. The analyzed result by using STORET method showed the quality statue of L.Sentani are ranged from moderate to heavy pollution in category since 2006.